How deep did Brexit & other factors influence exchange rates and how might these factors lead to further appreciation or depreciation on GBP - Chan, Chen Yuan (2017)
Exchange rate plays an important role in international trade, which is seen as an indicator of economic condition and national strength. The main goal of this paper is to discuss impacts caused by the recent Brexit issue to the UK’s exchange rates by using latest official statistics data. Through the analysis and discussion of different aspects including following headings can we have a clearer picture of the possible future between the UK and the EU, and how does it affect the exchange rate of GBP. 1. Inflation Rates 2. Interest Rates 3. Import and Export, 4. Global Reserve, 5. Penalties for Brexit 6. Functions of Central Bank The essay then concludes that in order to boost the UK’s economy, reduce the uncertainty and stop the further depreciation of GBP, the UK government should seek for staying in the European single market, in order to do that, there would certainly be some compromise and sacrifice need to be done by the UK such as early agreement with the EU for Brexit bill. At the same time, both sides should also soften their attitude toward each other to find an acceptable bilateral deal as soon as possible.